Seçilen Bir Ortam İçin Isıl Konfor Seviyesinin Belirlenmesi - Koyun, Tansel (Fırat University, 2016)
Canlılar ve özellikle de insanların yaşadığı ortamlarda ısıl konfor şartlarının sağlanması iş verimi açısından önemlidir. İnsan vücudu enerji üreten ve tüketen bir sistemdir. İnsan ancak ürettiği ve tükettiği enerji arasında enerji dengesi kurabilir ve vücut sıcaklığını 37°C de sabitleyebilirse kendisini rahat hisseder ve ısıl konfora ulaşır.Isıl denge sağlanıncaya kadar vücut ve ortam arasında farklı ısı transferi mekanizmaları oluşmaktadır.Bu çalışmada ısı transferi dikkate alınarak ısıl konfor parametreleri ayrıntılı olarak incelenmiş, örnek olarak seçilen bir ortama göre konfor seviyesi hesaplanmış ve çıkan sonuçlar tablolar ve diyagramlar halinde verilmiştir.

Ensuring the living conditions and comfort that especially in environments where people live is important in terms of work efficiency. The human body is a system of producing and consuming energy. But if people can set up energy balance between the energy generated and consumed, body temperature that can also fixed at 37 ° C feel comfortable, It reaches thermal comfort. It consists of different heat transfer until it reaches a thermal equilibrium between the human body and atmosphere.In this study considering the heat transfer ,thermal comfort parameters were examined in detail, according to the selected environment comfort level is calculated by selected sample and the results are showed in tables and diagrams.
Determination of TheThermal Comfort Level For A Selected Environment